Analysis of a Tall Structure Considering Shear Wall with Dampers and Bracings Considering Lateral Load Using ETABS - Shubham Soni; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2021)
Seismic analysis is mandatory in every case of structure analysis whether it’s related to any soil condition or geography. Architectures and structure engineers together have created marvels in form of unique structures whether its time from ancient Pyramids to Transamerica Pyramid in San Francisco. This structures are not always about cosmetic interests as even such structures are meant to be stable against different forces and economical aspects. High rise buildings and skyscrapers are designed with different technologies to resist heavy winds and seismic forces and such technologies include leaning at different angles, twisting shapes or creating free shapes for aerodynamics. Shear-wall are considered as the lateral load resisting members capable of resisting vibration from the ground or lateral forces. In this investigation, the results of maximum response in terms of base shear, displacement, forces are evaluated. The aim of this research designing and analysis of tall structures with shearwall in combination with bracings and dampers to improve the dynamic of the building. The seismic analysis of G+18 storey RCC building is considered considering seismic zone V, for analysis and design etabs software is utilized.